2009
DOI: 10.1245/s10434-008-0278-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatments and Prognoses of Patients with Combined Hepatocellular Carcinoma and Cholangiocarcinoma

Abstract: Patients with combined hepatocellular carcinoma and cholangiocarcinoma had poor postoperative survival rates. High CA 19-9 level was associated with poorer survival, suggesting that the cholangiocarcinoma portion may be a major determining factor for patient prognosis. Aggressive surgical treatment, including lymph node dissection, may improve survival in patients suspected of or diagnosed with these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 22 publications
8
107
3
Order By: Relevance
“…[4][5][6][7] Most literature on this topic is descriptive in nature, consisting of case reports and small series. Consequently, data regarding surgical outcomes for cHCC-CCA are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Most literature on this topic is descriptive in nature, consisting of case reports and small series. Consequently, data regarding surgical outcomes for cHCC-CCA are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported data suggested that the etiologic factors responsible for cHCC-CC are quite similar to classical HCC. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, our case exhibited a different cause -effect relationship from that reported in the literature, with a previous history of acquired biliary abnormality and hepatolithiasis. Abnormalities of the biliary tree and hepatolithiasis are the well-known risk factors for CC.…”
Section: Discussionmentioning
confidence: 74%
“…Hepatitis C infection is the second most common risk factor for the development of cHCC-CC. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, the association of viral hepatitis with cHCC-CC was lower than for HCC and higher than for CC. 19 Etiologic factors with a weaker association include alcohol consumption, liver fl ukes, and genetic hemochromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, commonly combined liver cirrhosis has the potential for serious complications, so strict selection of patients is required, taking into consideration any pre-existing cirrhosis, general physical condition, tumor extent as examples (6,11,12). Currently, aggressive treatments including liver transplantation have been attempted on cHCC-CC patient (13).…”
Section: Discussionmentioning
confidence: 99%